2022
DOI: 10.1007/s13132-022-00992-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Technology Investment Level on European Banks’ Profitability

Abstract: This paper examines the dynamic relationship between fintech investments and financial performance, and it explores whether the bank size could influence the performance in the context of the digital transformation (digitization). The fully modified ordinary least squares (FMOLS) model is estimated for 23 European banks throughout the whole period ranging from 2010 to 2019 and for the two sub-periods spanning from 2010 to 2014 and from 2015 to 2019. The econometric results evince that fintech are positively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
0
28
1
2
Order By: Relevance
“…Financial technologies have the potential to reduce costs by maximising economies of scale, increasing the speed and security of transactions, but at the same time authorities and policy makers need to establish new regulations to enhance the integration of these new financial technologies by banks and consequently improve the stability and prosperity of the financial sector. However, legislation also needs to be similarly strengthened to supervise banks in the area of environmental technology and to guarantee the security of the new services and products developed for consumers (Chhaidar et al, 2022).…”
Section: Research Resultsmentioning
confidence: 99%
“…Financial technologies have the potential to reduce costs by maximising economies of scale, increasing the speed and security of transactions, but at the same time authorities and policy makers need to establish new regulations to enhance the integration of these new financial technologies by banks and consequently improve the stability and prosperity of the financial sector. However, legislation also needs to be similarly strengthened to supervise banks in the area of environmental technology and to guarantee the security of the new services and products developed for consumers (Chhaidar et al, 2022).…”
Section: Research Resultsmentioning
confidence: 99%
“…A growing body of literature has focused on the relationship between banks' digitalisation and their performance. While some studies have found a positive relationship between banks' technological investments and performance (Casolaro & Gobbi, 2007; Chhaidar et al., 2022; Chowdhury, 2003; Kozak, 2005), others have not found such a relationship (Beccalli, 2007; Borello et al., 2022; Markus & Soh, 1993). These conflicting results highlight the challenge of objectively determining a bank's level of technological digitalisation and how it affects performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With data from industrial and commercial banks in China, their study showed that fintech has a U-shaped impact on bank profitability such that in its initial stages, it reduces bank performance and gradually increases bank performance over time. By applying the fully modified ordinary least squares model, Chhaidar et al (2022) studied the effect of the investment level of fintech on the profitability of 23 European banks from 2010 to 2019. The results of their study showed that financial technology has a significant positive effect on bank profitability.…”
Section: Literature Reviewmentioning
confidence: 99%